(9-x)(9-x)=17

Simple and best practice solution for (9-x)(9-x)=17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9-x)(9-x)=17 equation:


Simplifying
(9 + -1x)(9 + -1x) = 17

Multiply (9 + -1x) * (9 + -1x)
(9(9 + -1x) + -1x * (9 + -1x)) = 17
((9 * 9 + -1x * 9) + -1x * (9 + -1x)) = 17
((81 + -9x) + -1x * (9 + -1x)) = 17
(81 + -9x + (9 * -1x + -1x * -1x)) = 17
(81 + -9x + (-9x + 1x2)) = 17

Combine like terms: -9x + -9x = -18x
(81 + -18x + 1x2) = 17

Solving
81 + -18x + 1x2 = 17

Solving for variable 'x'.

Reorder the terms:
81 + -17 + -18x + 1x2 = 17 + -17

Combine like terms: 81 + -17 = 64
64 + -18x + 1x2 = 17 + -17

Combine like terms: 17 + -17 = 0
64 + -18x + 1x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '-64' to each side of the equation.
64 + -18x + -64 + x2 = 0 + -64

Reorder the terms:
64 + -64 + -18x + x2 = 0 + -64

Combine like terms: 64 + -64 = 0
0 + -18x + x2 = 0 + -64
-18x + x2 = 0 + -64

Combine like terms: 0 + -64 = -64
-18x + x2 = -64

The x term is -18x.  Take half its coefficient (-9).
Square it (81) and add it to both sides.

Add '81' to each side of the equation.
-18x + 81 + x2 = -64 + 81

Reorder the terms:
81 + -18x + x2 = -64 + 81

Combine like terms: -64 + 81 = 17
81 + -18x + x2 = 17

Factor a perfect square on the left side:
(x + -9)(x + -9) = 17

Calculate the square root of the right side: 4.123105626

Break this problem into two subproblems by setting 
(x + -9) equal to 4.123105626 and -4.123105626.

Subproblem 1

x + -9 = 4.123105626 Simplifying x + -9 = 4.123105626 Reorder the terms: -9 + x = 4.123105626 Solving -9 + x = 4.123105626 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + x = 4.123105626 + 9 Combine like terms: -9 + 9 = 0 0 + x = 4.123105626 + 9 x = 4.123105626 + 9 Combine like terms: 4.123105626 + 9 = 13.123105626 x = 13.123105626 Simplifying x = 13.123105626

Subproblem 2

x + -9 = -4.123105626 Simplifying x + -9 = -4.123105626 Reorder the terms: -9 + x = -4.123105626 Solving -9 + x = -4.123105626 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + x = -4.123105626 + 9 Combine like terms: -9 + 9 = 0 0 + x = -4.123105626 + 9 x = -4.123105626 + 9 Combine like terms: -4.123105626 + 9 = 4.876894374 x = 4.876894374 Simplifying x = 4.876894374

Solution

The solution to the problem is based on the solutions from the subproblems. x = {13.123105626, 4.876894374}

See similar equations:

| 166=2x-3(6x+18) | | 6x^2+14x-9x-21= | | 7r+4=2r+20 | | -4/9z=-3/5 | | 4x-9=5x+4 | | -48-14x=-202 | | 2ix^2+x+15i=0 | | 4.5=2x+3 | | 2x=429 | | 3-5n+3n=35-72 | | 5(x+7y)-8(6+y)= | | 60x^2+120x=0 | | -7+2x=9 | | X^5+36x=0 | | X^2+5x^2+4=0 | | 20-3x=5+2x | | x+x+8=26 | | x-5=1-2x | | -6(x+5)-44=2-22 | | 20x^3+60x^2=0 | | -11+2x=7 | | y+63x^3-75x^2+18x=0 | | 2(-2)+4y=-8 | | 2x-12+6x-21=6x+21 | | y=63x^3-75x^2+18x | | -5/6w=-16.5 | | 2*3.14x=44 | | 4(7b-8)+8=-3+7(7b+3) | | 0.5(x-8)=20 | | .9x=8.1 | | 3x-5+2x=40 | | 1/2h*13=130 |

Equations solver categories